ANALYSIS AND IMPACT OF THE INTERNET OF THINGS ON THE FUTURE OF AGILE PROJECT MANAGEMENT (Al-Aasar, 2025)
The Internet of Things (IoT) promises to reform project management through facilitating device interaction and data sharing, automating processes, and enhancing communication and collaboration among team members. However, this also raises numerous issues, such as managing the complexity of IoT devices, ensuring interoperability, and addressing data security and privacy concerns. In addition to providing explanations and best performs for establishing and management IoT organizations in this situation, this article also addresses the pros and cons of IoT in project management. This research utilized a questionnaire survey. Based on the semi-structured interviews conducted for this study, the IoT has the potential to bring important benefits to project management, with reduced costs, increased productivity, and improved teamwork and communication. However, these welfares can only be realized through careful planning, design, and management systems that successfully address interoperability, system complexity, and privacy and data security issues. Key lessons learned include: properly managing data and devices, thoroughly testing systems, and taking a holistic view of the user experience.